Spatial distribution of housing liquidity - Francisco Osswald do Amaral; Mark Toth; Jonas Zdrzalek (Kiel Institute for the World Economy (IfW Kiel), 2025)
This paper examines the relation between location, liquidity, and prices in urban housing markets. We build geospatial datasets for German and U.S. cities and show that housing liquidity and prices jointly decrease with distance to the city center. Using transaction-level data, we estimate a spatial housing search model and show that the cost of travel to the city center determines the joint spatial distribution of housing liquidity and prices. In a counterfactual analysis, we find that frictional illiquidity lowers prices in the outskirts by 7% relative to the city center and explains 19% of the spatial price gradient.
Keywords: G12; G51; R21; R30; 330; housing liquidity; housing prices; cities; spatial equilibrium; housing demand